Determinants of Frailty Status in Elderly Patients with Permanent Pacemakers at Adam Malik Hospital, Medan - Irawan, Raja Alfian; Ariestine, Dina Aprilia; Lubis, Anggia Chairuddin; Sungkar, Taufik; Nasution, Melati Silvanni (CoinReads Media Prima, 2025)
Introduction: Frailty is highly prevalent among elderly patients following permanent pacemaker implantation, with rates exceeding 70%. The Comprehensive Geriatric Assessment (CGA) evaluates frailty through domains such as nutrition (Mini Nutritional Assessment, MNA), comorbidities (Charlson Comorbidity Index, CCI), functional status (Barthel Index), cognition (Mini Mental State Examination, MMSE), mood (Geriatric Depression Scale, GDS), quality of life, polypharmacy, and pacemaker implantation duration, alongside sociodemographic factors like age and sex. Identifying factors influencing frailty is essential for optimizing outcomes and quality of life in this population. Methods: This cross-sectional study included patients aged ≥60 years with permanent pacemakers attending the Arrhythmia Clinic at Adam Malik Hospital, Medan, from October to December 2024. Frailty was assessed using the CGA. Bivariate analyses employed Fisher’s exact test and chi-square tests to evaluate associations between frailty scores and variables including MNA, CCI, Barthel Index, MMSE, GDS, quality of life, polypharmacy, implantation duration, age, and sex. Multivariate logistic regression was used to identify significant predictors of frailty. Results: Of 62 participants, 62.9% were aged 60–74 years. Bivariate analysis revealed that 58.1% of malnourished patients (per MNA) were frail (p<0.008), and 94.1% of those on polypharmacy regimens were frail (p<0.001). Multivariate analysis identified polypharmacy as the only significant predictor of frailty (OR 14.0; 95% CI 2.186–89.675). Conclusion: Nutritional status and polypharmacy are associated with frailty in elderly pacemaker patients, with polypharmacy showing a significant independent effect. Targeted interventions addressing polypharmacy may improve frailty outcomes in this population.